Genome-wide association study identifies a new melanoma susceptibility locus at 1q21.3 - MacGregor, Stuart; Montgomery, Grant W; Liu, Jimmy Z; Zhao, Zhen Zhen; Henders, Anjali K; Stark, Mitchell; Schmid, Helen; Holland, Elizabeth A; Duffy, David L; Zhang, Mingfeng; Painter, Jodie N; Nyholt, Dale R; et al. (Nature genetics, 2011)
Stuart MacGregor and colleagues report the results of a genome-wide association study for melanoma susceptibility in an Australian population. They identify a new melanoma susceptibility locus on chromosome 1. We performed a genome-wide association study of melanoma in a discovery cohort of 2,168 Australian individuals with melanoma and 4,387 control individuals. In this discovery phase, we confirm several previously characterized melanoma-associated loci at MC1R , ASIP and MTAP – CDKN2A . We selected variants at nine loci for replication in three independent case-control studies (Europe: 2,804 subjects with melanoma, 7,618 control subjects; United States 1: 1,804 subjects with melanoma, 1,026 control subjects; United States 2: 585 subjects with melanoma, 6,500 control subjects). The combined meta-analysis of all case-control studies identified a new susceptibility locus at 1q21.3 (rs7412746, P = 9.0 × 10 −11 , OR in combined replication cohorts of 0.89 (95% CI 0.85–0.95)). We also show evidence suggesting that melanoma associates with 1q42.12 (rs3219090, P = 9.3 × 10 −8 ). The associated variants at the 1q21.3 locus span a region with ten genes, and plausible candidate genes for melanoma susceptibility include ARNT and SETDB1 . Variants at the 1q21.3 locus do not seem to be associated with human pigmentation or measures of nevus density.